Uma proposta de método para especificação de componentes de software - Almeida Junior, José Valdvogel de (2015)
The component-based software development has proven effective for implementation in various fields of application, but still insufficient to create reusable and flexible parts. Processes and methods have been developed in order to address special care in this context. However, none of the proposed methods shows a simple specification of building blocks. To address this limitation we propose in this research work a split between the static and dynamic elements that make up the nature of an assembled component in a set of steps with application techniques using the best practices of software engineering. As a result, we reach the Component Specification method capable of generating well-designed models for building reusable and flexible software parts. A case study helps to illustrate the application of the method in an application context